Implementasi Kebijakan Peraturan Walikota Surabaya Nomor 106 Tahun 2022 Tentang Tata Cara Pengumpulan, Pengolahan dan Pemanfaatan Data Keluarga Miskin: Studi di Kecamatan Krembangan Kota Surabaya - Efida Aprilia H. A; Agus Widiyarta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out the extent of the implementation of Perwali Policy number 106 of 2022 in the City of Surabaya. This research uses descriptive qualitative research methods. The communication contained in policy implementation is two-way communication from the Social Service to the community and to the relevant SKPD in the Surabaya area. Resource factor, from this indicator it can be seen that the existing resources in the sub-districts, Surabaya City Social Service, RW and RT in the Krembangan District area include staff, information, authority and facilities which are quite good. Disposition factor, from this indicator it can be concluded that the disposition carried out by the sub-district in Krembangan District and the Surabaya City Social Service includes cognition, direction and response which is quite good with employee responses being quite responsive. From this indicator it can be concluded that the sub-districts in Krembangan District, the Surabaya City Social Service, RT and RW in the Krembangan District area have implemented Standard Operating Procedures (SOP) for the implementation of data collection on the Poor (GAKIN).